Ohuka landslide, New Zealand: a low angle bedding-controlled coastal landslide at Port Waikato, North Island, New Zealand. Issue 2 (3rd April 2022) - Bevan, David; Beresford, Joanna; Arthurs, James; Gasston, Caleb; Brook, Martin S.; Prebble, Warwick; Brideau, Marc-Andre
ABSTRACT: Overseas, relict deep-seated coastal landslides have attracted significant analysis because of potential hazards caused by sea level rise and climate change. Despite the rapid growth in the Auckland region, regional coastal landslide hazards are poorly understood. We investigated the geomorphology and material properties of Ohuka coastal landslide on the southwestern coastline of the Auckland region, to better understand the failure mechanism. The site is formed on weak Neogene sediments of varying lithological properties, with very low angles of dip, exposed on both the seaward (west) and landward (east) flanks of Ohuka Hill. Displacement appears to have been rotational, along a low-angled basal shear surface, the Koheroa Clay Seam. The surface geomorphology consists of discontinuous uphill-facing scarplets indictive of rotational slump blocks, along the basal shear surface. However, the preservation of slump block surface topography is hindered due to the lack of a thick, strong caprock, and high annual rainfall (1400 mm), and erosion. The proposed failure mechanism and general geometry is consistent with correlations between graben width and depth to failure plane reported from bedding-controlled coastal landslides formed on low dip angles in southern England. This provides important context, given the paucity of New Zealand bedding-controlled coastal landslide case studies.